Kiwanuka [compact disc] - Kiwanuka, Michael, 1988- (Interscope, 2019)
London native Michael Kiwanuka has won over the hearts of many with his soulful voice & trademark 'modern vintage' sound. Drawing inspiration from Curtis Mayfield, Jimi Hendrix, Ron Isley & more, his 2016 album Love & Hate was received to mass critical acclaim with rave reviews from The New York Times, Pitchfork, NPR, Rolling Stone & more, debuted at number one on the UK chart, and earned him a Mercury Prize nomination.